Penyuluhan dan Deteksi Infeksi Saluran Kemih pada Pekerja Wanita - Donatila Mano S; Nimas Berlian Betta Chantika; Yohanes Firmansyah; Halim Santoso (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Urinary tract infection (UTI) in women occurs when bacteria or other microorganisms infect parts of the urinary tract, such as the urethra, bladder, ureters, or kidneys. UTIs are more common in women due to the shorter anatomy of the female urethra and closer to the anal area, which allows bacteria to enter the urinary tract more easily. Community education and detection of urinary tract infections in female workers are important activities to increase awareness, prevention and early detection of this condition. Extension activities provide appropriate knowledge about the causes, symptoms, and steps to prevent UTIs. In addition, early detection through urine examination helps in finding UTI cases early and taking appropriate treatment measures. This activity brings long-term benefits, such as reducing work absenteeism and increasing productivity. By raising awareness and providing good understanding, women workers can take effective prevention measures. Community education and detection of UTIs in female workers is important for improving their health and quality of life, as well as reducing the burden that UTIs place on individuals and society as a whole.